Accurate differentiation ofMycobacterium chimaerafromMycobacterium intracellulareby MALDI‐TOF MS analysis. Issue 5 (May 2017) - Pranada, Arthur B; Witt, Ellen; Bienia, Michael; Kostrzewa, Markus; Timke, Markus
Abstract : Purpose. : The increasing number of infections caused by nontuberculous mycobacteria (NTM) has prompted the need for rapid and precise identification methods of these pathogens. Several studies report the applicability of MALDI‐TOF mass spectrometry (MS) for identification of NTM. However, some closely related species have very similar spectral mass fingerprints, and until recently, Mycobacterium chimaera and M. intracellulare could not be separated from each other by MALDI‐TOF MS. Methodology. : The conventional identification methods used in routine diagnostics have similar limitations. Recently, the differentiation of these two species within the Mycobacterium avium complex has become increasingly important due to reports of M. chimaera infections related to open heart surgery in Europe and in the USA. In this report, a method for the distinct differentiation of M. chimaera and M. intracellulare using a more detailed analysis of MALDI‐TOF mass spectra is presented. Key Findings. : Species‐specific peaks could be identified and it was possible to assign all isolates (100%) from reference strain collections as well as clinical isolates to the correct species. Conclusions. : We have developed a model for the accurate identification of M. chimaera and M. intracellulare by MALDI‐TOF MS. This approach has the potential for routine use in microbiology laboratories, as the model itself can be easily implemented into the software of the currently available systems by MALDI‐TOF MS manufacturers.